Análise dos processos e instrumentos de ordenação do território: comparação entre Brasil e Portugal - Dainezi, Plínio Marcos [UNESP] (2014)
When analyzing the politics of urban development in Brazil and Portugal aim to promote more environmentally sustainable and quality of life urban environments, as well as the development of the social functions of the city and the welfare of its inhabitants. Developing cities ensuring these objectives implies spatial planning across an urban public policy capable of responding to changing urban space, including the fragmented and dispersed urban sprawl through distant settlements of the consolidated urban area, creating voids and urban areas rarefied occupation intervals between dwellings that remain unused. In Brazil, the Law 10.257/01 has the municipal government urban policy instruments that can be applied to urban land use and control this problem. In the Portuguese case control policy and planning of urban expansion occurs through programs, plans and legal instruments. Brazil and Portugal in recent years showed distinct to control urban sprawl instruments. The Portuguese model is composed of a national program of regional planning, regional land-use planning, municipal directors cloths political, and legal regimes without appearing in the master plans. In Brazil the main instruments are offered by the Statute adopted in 2001 and implemented through master plans, but the creation of more compact cities will not appear as the aim of territorial planning and management. However, the control exercised in the Portuguese urban areas and the lack of municipal programs of urbanization has led to fragmentation of urban to rural areas through strategies of the housing market for the approval of projects in urban and rural areas